Analysis of Tuna Fish Resource Management (Thunnussp) on a Sustainable basis at Fish Landing in Bontotiro District Bulukumba Regency - Eka Ratu, Andi; Sudirman, Sudirman; Yanuarita, Dewi (International Journal of Environment, Agriculture and Biotechnology, 2019)
This study aims to determine the management of the sustainability of tuna resources in Bulukumba Regency using the EAFM approach. This research was conducted in the waters of the Gulf of Bone by taking a fishing base location at the Fish Landing Port (PPI) of BontoTiro, Bulukumba Regency for four months, which began in December 2018 to March 2019. Analysis of data used in this study using 6 EAFM dimensions and assisted with Rapfish software. The results of the study show that some dimensions have a fairly good sustainability value (> 50%), namely on the social dimension (57.1%), Habitat and ecosystem (57.25%) and dimensions of fish resources (51.88%). Tuna fishing activities that focus on the management of fisheries resources must be able to cover the regulation of fish resource use environmental management, and human activities in its management. In the smallest dimension in sustainable management, tuna is in the economic dimension with a value of 29.56% or in the bad category. This needs special attention from the local government of Bulukumba Regency, as well as at the provincial and central levels in raising the economic level of fishing communities working on tuna fishing. There needs to be government policy and innovation in providing assistance and providing alternative new livelihoods and tuna processing which can have a significant impact on improving the welfare of fishing.